Rahab and her visitors: reciprocal deliverance - Biddle, Mark E. (Word & world, 2017)
Who are the heroes and who are the saviors in the story of Rahab? There are spies who do not spy and messengers with no message, but the Israelites end up hearing their own theology preached to them from an "outsider".Joshua 2 is a story where all the lines are blurred.